Research of Parameterized Modeling and Finite Element Simulation of Locomotive Traction Gear - Xuan Liang; Ding Haichun; Lei Lei; Guan Tianmin; Li Zhenjun (Jixie chuandong)
The locomotive traction gear is the key component to power transmission and speed control of locomotive drive system,which plays a key role in locomotive running speed and Bearing torque. With the need of different locomotive design,the parameterized modeling of the traction gear can effectively reduce the development cycle. The formation equation of involute tooth profile and transition curve is introduced,and the tooth profile modeling is carried out in the SolidWorks 3 D modeling software environment by Program-driven method. Taking a certain type of locomotive traction gear as an example,the finite element simulation of the gear is carried out. The comparison and analysis of the contact stress of the tooth surface and the bending stress of the tooth root are compared with the theoretical results,and the accuracy and rationality of the design and modeling of the traction gear is verified. It is of great value to the rapid design and simulation of the traction gear.